Biodecolorization and Biodegradation of Methylene Blue Dye by Gloeophyllum trabeum and Fenton-Like Reaction - Purnomo, Adi Setyo; Rizqi, Hamdan Dwi; Kuncoro, Wahyu Adhy; Rohmah, Alya Awinatul; Tsutsumi, Yuji (Indonesian Journal of Chemistry, 2026)
This study investigated the potential of the brown-rot fungus Gloeophyllum trabeum to decolorize and degrade methylene blue (MB) through a synergistic Fenton-like mechanism. The main objective was to elucidate the contribution of the Fe2+-dependent Fenton-like reaction of G. trabeum in enhancing the efficiency of MB biodegradation. Decolorization experiments were carried out in mineral salt medium (MSM) with and without FeSO4 supplementation for 0, 7, 14, 21, and 28 d of incubation. The results showed that the addition of Fe2+ significantly accelerated MB decolorization, achieving 91.9% efficiency compared to 88.3% without Fe2+. LC–MS analysis identified two major degradation metabolites, C14H16N2O3S and C12H11N3O7S, indicating oxidative demethylation and thiazine-ring cleavage as key degradation pathways. The findings suggest that G. trabeum employs a dual mechanism involving both Fenton-like radical generation and enzymatic oxidation, where Fe2+ addition further enhances its decolorization and degradation capability. Hence, this study demonstrates that the Fenton-like reaction of G. trabeum represents an effective and environmentally sustainable approach for the remediation of synthetic dye pollutants.